2016
DOI: 10.1177/0961203315627202
|View full text |Cite
|
Sign up to set email alerts
|

Overall and cause-specific mortality in systemic lupus erythematosus: an updated meta-analysis

Abstract: Patients with SLE had higher rates of death from all causes, regardless of sex, ethnicity, renal disease, CVD or infection. However, the risk of death due to malignancy was not increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
183
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(206 citation statements)
references
References 30 publications
11
183
1
11
Order By: Relevance
“…However, the overall frequency of fatal infections is in agreement with reports on SLE cohort studies worldwide, where infections also make up approximately a third of all fatalities. 28,29 The rate of ESRD-related death was higher than reported elsewhere and this may be due to comorbidity, accessibility and/or reluctance to start and continue renal replacement therapy as illustrated by the two IA patients that chose to discontinue dialysis.…”
Section: Discussionmentioning
confidence: 93%
“…However, the overall frequency of fatal infections is in agreement with reports on SLE cohort studies worldwide, where infections also make up approximately a third of all fatalities. 28,29 The rate of ESRD-related death was higher than reported elsewhere and this may be due to comorbidity, accessibility and/or reluctance to start and continue renal replacement therapy as illustrated by the two IA patients that chose to discontinue dialysis.…”
Section: Discussionmentioning
confidence: 93%
“…10,24,25 Esto lo encontramos en el grupo B en forma más frecuente y con diferencia significativa en las siguientes manifestaciones hematológicas: trombocitopenia (25% de los niños contra 7.7% del grupo A), anemia (30.6% contra 15.4%) y alteraciones leucocitarias (44% contra 7.7%).…”
Section: Discussionunclassified
“…Se hizo el cálculo de frecuencias y porcentajes, así como pruebas de hipótesis para encontrar asociaciones significativas entre el grupo etario de los pacientes y las entidades clínicas reportadas empleando la prueba de c 2 y, en caso de ser necesaria, cuando en alguna de las categorías el número de pacientes fuera inferior a cinco, se utilizó la prueba exacta de Fisher. Además, para las principales manifestaciones clínicas que se asociaron con la mortalidad de los pacientes con LES [6][7][8][9][10][11][12][13] se obtuvieron las razones de momios (RM) y sus respectivos intervalos de confianza al 95% para conocer el riesgo en los niños para padecer comorbilidades, comparados con el grupo de adultos.…”
Section: Análisis Estadísticounclassified
“…10,11 Lee et al found that patients with SLE have a 2.6-fold higher mortality rate compared to an age-matched and sex-matched general population. 12 Indeed, it is known that patients with SLE have a propensity for accelerated coronary artery disease. 13,14 Yet these patients have been difficult to risk stratify, and the current cardiac risk scores only take into account traditional risk factors for atherosclerotic disease such as hypertension, diabetes mellitus, and smoking.…”
Section: Introductionmentioning
confidence: 99%